#TITLE_ALTERNATIVE# - SALAM , ANWARUS
This final project discuss about monochromatic wave propagation along the channel with a base of porous media long and flat. This problem is seen as 2- dimensional flow. Flow in porous media and in the upper layer assumed ideal and irrotational. Using this assumption, the velocity of fluid particles in both layers can be expressed as two potential functions and of course different. Characteristics of porous media, namely the porosity affects the effective velocity in porous media. Linear model of the governing equations is used to observe the propagation of monochromatic waves. Linear model of two boundary problems of Laplace equation is solved using boundary conditions. Wave elevation timedependent variable along the channel in the form of monochromatic waves and dispersion relation derived from the linear model used to observe the wave propagation along the channel. Wave frequency, depth, porosity, thickness of porous media, and drag force in porous media play an important role on the damping of the amplitude.